Legacy of mercy [large type] - Austin, Lynn N. (Austin, Lynn N. Waves of mercy novel., 2018)
Young socialite Anna Nicholson is having trouble focusing on her upcoming marriage due to lingering questions about her birth mother. After hiring detectives to learn more about the past, Anna decides that some secrets are better left hidden. Her choice to seek God's purpose for her life also isnt as simple as she had hoped. But Anna knows she can turn to her grandmother, Geesje de Jonge, back in Holland, Michigan. Geesje's been helping new Dutch immigrants - including a teen with a troubled history - adjust to America. She only hopes that her wisdom can help all these young people through the turmoil they face.